(3QSGdI aj HjGf GdCQcGfs ((3CjhH Hf YKeGf Hf YeQ s)
(3ChdgG (B:s
(3HYO GdHSedI hGdMeO dg GdaUd GdChd ai GdfGQ hajg KdGKI eHGMK GdHMK GdChd ai GKHGJ chI GdfGQ , GdLSe GdbGHd ddSNhfI ehLH dShfJg s
(3BNQgG (B:s
(3hEPG YGOJ Edi GdMGdI GdWHjYjI cGfJ hCeG HjGf cPH GdYGdj aCfg dh MUd gfGc gfGc cQI aCeG Cf Jchf MeGSI dcQI GdYGde Ch de Jchf s
(3Vef eLehY , JQJjHgG (B: 6s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs